Optimization drilling process of glass fiber reinforced plastics - Norhaida, Mohamad Noor (2008)
Fibre reinforced composites are widely recognized for their superior mechanical properties and advantages for applications in aerospace, defence and transportation sectors. The material that was being chosen for this research is glass fibre reinforced plastics. Drilling tests have been conducted on glass fiber-reinforced plastic composite glass fibre reinforced plastic laminates using an instrumented CNC milling center. Machining parameters such as type of drilling tool, feed rate, cutting speed, and their influence on the thrust force are investigated. Furthermore, the quality of the holes produced from the drilling process also must be considered with special attention paid to the delamination damage.The damage was seeing through optimal microscope. Kistler software was been using to get the trust force value as the output in this experiment. The Kistler Piezoelectric Dynometer was connected to the PC of CNC machine. The function is to measure the thrust force value. The delamination factor can be calculated by using their equation. By using SPSS software to get the equation, the equation that was being created is Multiple Linear Regression then come out with ANOVA analysis. This equation is to show that the significant of the variables when drilling glass fiber. After that, User-Defined was being used to optimize the parameter and get the optimal condition to drill glass fiber for minimized the damages.